The Minangkabau Traditional Architecture on the Roof of the Rao Rao Mosque in the 20th Century AD - Rahmat, Syahrul; Abd Rahim, Siti Azira (Journal of Educational Review and Cultural Studies, 2023)
The Rao Rao Mosque in Tanah Datar, West Sumatra is an ancient mosque built in the early 20th century AD. The roof of this mosque is gonjong, a roof shape commonly found in Minangkabau traditional buildings, both rumah gadang (traditional house) and balai adat (traditional halls). The shape of the roof is different from the shape of mosque roofs in general, both in Minangkabau and other Islamic countries. This research aims to analyze the influence of traditional Minangkabau architecture on the roof of the Rao Rao Mosque along with its meaning. This research was carried out within the framework of case study research. Physically, the roof of the Rao Rao Mosque is clearly influenced by the roofs of traditional Minangkabau buildings. The use of this roof shape also has a philosophical meaning related to the traditional philosophy and life of the Minangkabaunesse. Apart from that, the Rao Rao Mosque keeps a cultural track record of the Minangkabau people at the beginning of the 20th century which is stored in the form of values in its architecture.